Representation of Major Female Characters as the Victim of Patriarchal Supremacy in F. Scott Fitzgerald’s ‘The Great Gatsby’ - Humagain, Sumargi (International Research Journal of MMC, 2026)
This study explores the position of the Female Characters in the patriarchal society of America in the 1920s through a subtle analysis of Francis Scott Fitzgerald’s novel, “The Great Gatsby”. The study primarily highlights major three female characters Daisy Buchanan, Myrtle Wilson and Jordan Baker, their status as the products of oppressive forces and objects rather than as thoughtful beings. The study is based on the qualitative research analysis and application of the feministic approach in order to interpret the aroused themes. The study thematically makes a rigorous and critical analysis of the novel’s significant phrases and statements taken from the novel. Thematic analysis rivets on the secondary data sources, including peer-reviewed journal articles and critical books on 20th-century American literature. The theoretical framework is based on feminism which illuminates the female characters’ leaning to marry well-off men and entangling them in morally wicked partners. The findings expose a shocking depiction of the women’s entrapment, offering important insights into how the American Dream utilizes the women as the commodities. This study pinpoints the critical significance of questioning against the historical patriarchal prejudicial treatments and stresses on the need of a contemporary re-consideration of systemic gender biases.